Common threads in a random tapestry: Another viewpoint on exertional heatstroke - Roberts, W. O. (The Physician and Sportsmedicine, 2005)
Issues surrounding heat illness remain somewhat controversial, and our understanding of exertional heatstroke is evolving. The ability of humans to compete and work in hot, humid conditions with a low incidence of exertional heatstroke demonstrates tremendous adaptability. On the other hand, the occurrence of exertional heatstroke in conditions that should be prime for all-out physical effort remains puzzling and problematic.